(untitled) (Current Problems in Rail Vehicles, 2021)
Definition of travel comfort. Rational and emotional relationships of passengers to transport systems and transportation. Harmony of public transport with emotions of a passenger. Emotional perception of a vehicle aesthetics, ergonomics of technical solution and transport process. Anthropological development of a human in the 20th and 21st century. Space and its perception by passengers, spatial requirements of seating. Systematic approach to minimizing the effects of vibration, noise, heat, light and indoor air quality on the comfort of the train occupant. Positive perception of public transport as a basic factor for exploiting a potential of extra-modal energy savings in replacing individual car transport with less energy-intensive and emission-free rail transport.